Pelaksanaan Pencatatan Perkawinan Beda Agama Sebelum dan Setelah Terbitnya SEMA Nomor 2 Tahun 2023 di Pengadilan Negeri Kota Yogyakarta - Rivani, Giska Natasya; Gunawan, Ade (Veteran Law Review, 2024)
The issuance of SEMA has an impact on interfaith marriage couples in Indonesia, especially on marriage registration. It should be noted that marriage registration is mandatory to obtain administrative documents such as marriage certificates, family cards and others. Prior to the SEMA, the Yogyakarta City District Court had granted the application for registration of interfaith marriages. The existence of the legalization of interfaith marriages by the Yogyakarta City District Court which then comes SEMA Number 2 of 2023 which clearly and explicitly prohibits interfaith marriages is interesting to be studied further. This research uses empirical legal research method with legislative approach and case approach. The results of this study show the basis of the judge's consideration in granting the registration of interfaith marriages in the Yogyakarta City District Court, including judges assessing the existence of a legal vacuum, the potential for misuse of social values, and providing legal certainty for children of interfaith marriage couples. The judge's consideration in granting this case is contrary to the provisions of Article 2 paragraph (1) of the Marriage Law. The implementation of this SEMA makes interfaith marriages unable to be registered at the Yogyakarta City District Court. The validity of the registration of interfaith marriages that have been carried out remains valid and applicable because a regulation is not retroactive. The implementation of this SEMA can be declared effective as evidenced by the absence of requests for registration of interfaith marriages at the Yogyakarta City District Court